Peran Masyarakat Desa Kaduengang dalam Pemberdayaan Agrowisata Saung Biru (Gunung Karang, Pandeglang) - Willy Handri; Iin Indiyani; Sriayu Purwa Lestari; Elin Marlina; Nasywa Nisrina Zalfaa; Rafli Febrian Susilo; Laura Laura; Retno Handayani; Ria Yuni Lestari (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2025)
The role of the community in empowering tourist villages means having similar thought patterns and patterns of action from rural communities regarding the potential that exists in their villages. Saung Biru is one of the tourist attractions located in Kaduengang, Cadasari District, Pandeglang, Saung Biru is one of the agro-tourism that prioritizes the concept of local community empowerment. This study aims to explore the role of the Kaduengang community in empowering Saung Biru Agrotourism, both in terms of management and its impact on their economic and social welfare. The role of the community in community empowerment activities in Kaduengang Village. Community empowerment activities are considered as a business learning process through the process of evaluating everything that has been achieved in the implementation of the business, as well as studying the various obstacles faced.